Pemanfaatan Lembar Kerja Peserta Didik (LKPD) Berbasis Etnomatematika Untuk Meningkatkan Pemahaman Soal Cerita Peserta Didik Kelas III/B SDN 05 Kestalan - Pranita Marta Dinata; Ema Butsi Prihastari (Universitas Negeri Padang, 2021)
This study was structured with the aim of increasing students' understanding of stories and learning outcomes using ethnomathematical-based LKPD media on standard unit material for class III students at SDN 05 Kestalan Surakarta Academic Year 2021 / 2022. The research subjects were students in class III B SDN 05 Kestalan Surakata which consists of 24 students. This type of research is Classroom Action Research (CAR), wherein in this study, the teacher is the executor of learning while the researcher is the observer. The research design used the research of Kemmis and Mc. The tags start from planning, reflection, cycle 1, and cycle 2, this research is carried out in the odd semester of the 2021/2022 academic year, which is in September – October. Data collection techniques by observation, tests, and interviews. The results showed an increase in each cycle on the average initial reflection of students by 61.2, the first cycle of 73.0, and the average of the second cycle of 81.0.